Human Papillomavirus 16 E6/E7 Oncoproteins Transfection: Identification of Acquired Robertsonian Translocations in Human Keratinocytes Involving Chromosomes 13, 14, and 15 - McGhee, Eva; Das, Sameeran; Handler, Adin; Handler, Julian; Palefsky, Joel (Archives of Clinical and Medical Case Reports, 2020)
Human papillomavirus16 (HPV) E6/E7 oncoproteins are associated with increased chromosomal instability through Robertsonian aberrations. Robertsonian translocations are common constitutional abnormalities in humans but are considered rare occurrences in cancer cells. Research is sparse surrounding Robertsonian translocations in viral infected cells; therefore, we examined whether HPV-E6/E7 transfection could facilitate the formation of Robertsonian aberrations. We used spectral karyotyping (SKY) and array-comparative genomic hybridization (array-CGH) to score Robertsonian aberrations in 16-MT cells, which were derived from human keratinocytes that were transfected with HPV16 E6/E7 oncoproteins. We analyzed 30 metaphases to determine the types of Robertsonian translocations present in the 16-MT cells. The results showed non-homologous Robertsonian translocations in 100% of metaphases scored and homologous acrocentric rearrangements-isochromosome types in 75% of metaphases scored. We studied two types Robertsonian translocations: der(13;14), the non-homologous type, and i(13), the homologous isochromosomes type. The results showed that HPV E6/E7 oncoproteins induce genomic instability, causing Robertsonian translocations on chromosomes 13 and 14. This analysis provides a reliable method for future research in the mechanisms of Robertsonian translocations as a result of centromeric fusion in HPV-transformed cells.